(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Spinal cord tumors are one of the most pressing problems in neurosurgery. Spinal cord tumors account for 2% of all neoplasms and 3% of nervous system pathology in adults[V.V. Stupak, S.V. Shabanov, I.V. Pendyurin, S.S. RabinovichResults of surgical treatment of patients with extramedullary hourglass tumors]. Most often, spinal cord tumors are observed in the socially active group of people aged 30–50 years, which determines the greater relevance of this problem.[V.V. Stupak, S.V. Shabanov, I.V. Pendyurin, S.S. RabinovichResults of surgical treatment of patients with extramedullary hourglass tumors]. Standardization of neurological examination and formulation of neurological conclusion in spinal trauma is a pressing issue in neurotraumatology, neurosurgery and neurooncology.Improvements in diagnostic methods and visualization of spinal cord structures, the development of microsurgical techniques and minimally invasive approaches have made it possible to significantly expand the indications for surgery and improve treatment results. But even differentiated choice of surgical approaches is required, which should ensure optimal visual control over the progress of tumor removal and the state of nerve structures with minimal displacement of the spinal cord.Thus, the search for new solutions and tactical and technical approaches in the treatment of spinal cord tumors, in particular intramedullary spinal cord tumors, has not lost its significance and is a subject for discussion in neurosurgical communities.